2006
DOI: 10.4103/0972-5229.24686
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with chest trauma: Where do we stand today

Abstract: Background and Aims: Chest trauma is a major public health problem in India, but only few studies have been conducted to analyze its magnitude and management. The present study was carried out to determine the epidemiological profile of chest trauma cases and to analyze the management strategies with an aim to identify the scope of improvement in our setup. Materials and Methods: It is a retrospective study of cases admitted with chest trauma, to a tertiary care hospital. Records of the patients admitted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…More than half of the patients (55.5%) were between 21 to 40 years. M. Mohta et al, (2) reported 49.55% patients in their study of 105 in the same age group (21-40 years). Massaga et al (3) had 43.75% patients from age group of 30 to 49 years.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…More than half of the patients (55.5%) were between 21 to 40 years. M. Mohta et al, (2) reported 49.55% patients in their study of 105 in the same age group (21-40 years). Massaga et al (3) had 43.75% patients from age group of 30 to 49 years.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…M. Mohta et al, (2) reported 785 of the patients out of 105 suffered blunt injuries in their study. Few studies have shown penetrating injuries to be the commonest cause of chest trauma.…”
Section: Tabular Description Of Chest Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have reported similar experience. 1,8,9 Increased automobile traffic and ever increasing population together with intentional or unintentional ignorance of traffic rules account for the predominance of road side accidents producing chest trauma. Right side lung was most commonly (58%) injured following chest trauma in our study, left side in 26% cases while bilateral involvement was seen in 16% cases.…”
Section: Discussionmentioning
confidence: 99%
“…Chest trauma constitutes about 10-15% of all the trauma cases and is responsible for 25% death due to trauma 1 . Trauma to chest may occur due to fall from height, road traffic accidents, assault or being hit by an object or an animal.…”
Section: Introductionmentioning
confidence: 99%